Case Study: The University of Teesside Learning Resource Centre: Access to Knowledge, Imagination & Learning - Butchart, Ian C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The University of Teesside is located in Middlesbrough, a major North East town at the heart of the Teesside region. Over 14,000 students are currently studying at Teesside on a range of courses, from diplomas and first degrees to postgraduate qualifications. The University’s £11 mill. Learning Resource Centre is at the heart of the Teesside learning experience and is a landmark for the region.